Nutritional status and dietary intake among Nigerian adolescent: a systematic review - Hadiza Abdullahi Abubakar; Mohd Razif Shahril; Sumaiyah Mat (BMC, 2024)
Abstract Introduction The prevailing nutritional conditions and the triple challenge of malnutrition faced by adolescents have adverse consequences for both the present and future generations' health and nutrition. Summarizing the available research on the nutritional status and dietary habits of adolescents in Nigeria is crucial. Objective This study aims to systematically evaluate available literature on the nutritional status of adolescent aged 10 to 19years in Nigeria. Methodology A systematic search using PRISMA guideline was conducted. Three electronic databases were searched i.e., PubMed, Web of Science and Scopus using specific terms and keywords for online articles published between 2013 and 2023. After applying specified inclusion and exclusion criteria, 51 articles were selected for data extraction, synthesis and quality assessment. Results Of the 51 included studies, 78.4% were conducted in the Southern Nigeria, 11.8% in the Northern Nigeria and 9.8% included both regions. The prevalence of overweight ranged between 0.8 and 31% and obesity ranged between 0.1 and 14%. The prevalence of thinness, stunting and underweight ranged between 3 and 31%, 0.4 to 41.6%, 0.3 to 73.3% respectively. The review also identified an inadequate intake of essential nutrients including iron, zinc, calcium, vitamin A, C, D, niacin, thiamin, riboflavin, cobalamin, and folate, with vitamin A deficiency prevalence ranges from 44 to 96%. The dietary patterns were characterized by a high consumption of cereals grains and starchy foods, low animal proteins, fast-food with soft drinks, and limited consumption of fruits and vegetables along with meal skipping. Conclusion These findings portray a complex picture of the nutritional challenges faced by this demographic group, highlighting both undernutrition and overnutrition, poor eating behaviour and micronutrient deficiency as significant concerns. The review revealed regional disparities in research representation, with a concentration of studies in Southern Nigeria. This highlights the importance of directing research efforts toward the northern regions, where the prevalence of nutritional issues is equally severe, but less studied. Systematic review registration number PROSPERO CRD42023481095.